Morphological evaluation of styloid processes and their correlation with gender and age using Multidetector Computed tomography - Sharma, Prakash; Lalchan, Subita; KC, Subhash; Gyawali, Merina; Paudel, Asheem; Koirala, Krishna (Journal of Brain and Spine Foundation Nepal, 2021)
Introduction: The styloid process (SP) extends inferiorly from the temporal bone. Many neurovascular structures are closely related to its tip. Alteration in the length, angle and morphology of styloid process may lead to symptoms related to neurovascular compression. Hence it is necessary to know the normal variations before delineating the exact cause of symptoms related to head and neck region. This study was conducted to assess the variations in length, angle and morphology of styloid process and to correlate it with gender and age group. Methods: The Patients of trauma undergoing Paranasal Sinus Computed Tomography (CT) scan who were otherwise asymptomatic prior to the trauma were included in the study. Images were evaluated in dedicated work station. Length of bilateral styloid process were measured. Angulation of the SP was defined in the coronal and sagittal planes, respectively and morphology was identified as type I, II, III and IV. Findings were correlated with gender and age group. Results: A total of 192 patients were included in the study. The age of the patients ranged from 13 to 86 years. Mean length of right styloid process was 26.6±8.6 mm and mean length of left styloid process was 27.0±8.2 mm. There was no significant difference between the length of styloid process in males and females. Males had a significantly larger coronal angle as compared to females. There was a linear, weak, positive correlation between the length of styloid process and advancing age. Conclusion: There was a wide variation in length, angle and morphology of styloid process.